The Haven Hood: Redefining Portable Units for Communities in Need - Nour Ksaiby; Doaa Ibrahim (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
According to the United Nations High Commissioner for Refugees, over a 100 million people worldwide were forcibly displaced from their homes, facing life-threatening poverty, suffering from overcrowding, lack of proper food and water, lack of sanitary methods, mental health challenges such as depression, anxiety, and post-traumatic stress disorder. This study provides a solution suitable for the temporary crisis: a shelter with essential units including residential, educational, healthcare, and outdoor facilities; to increase refugees' self-reliance and improve their life conditions. The best architectural solution for refugees follows transitional shelter typology, which has movable, adaptable, transformable, and interactive features. A shipping container provides a unit that has the previous features in addition to sustainable approaches and flexibility; this makes it the best choice to serve the study goal and to achieve the three main elements of this study, shelter, flexibility, and sustainability, creating a prototype that can adapt different needs.